Dual Z-scheme g-C3N4/Ag3PO4/Ag2MoO4 ternary composite photocatalyst for solar oxygen evolution from water splitting - Liu, Wei; Shen, Jun; Yang, Xiaofei; Liu, Qinqin; Tang, Hua (Applied surface science, 2018)
[Display omitted] •g-C3N4/Ag2MoO4/Ag3PO4 heterojunction photocatalyst was prepared.•The heterojunction showed enhanced photocatalytic oxygen evolution from water splitting.•The formation of dual Z-scheme system promotes the separation of photo-generated charges. Semiconductor-based solar-driven photocatalytic water splitting has been considered as one of the most promising solutions to solve the problem of fossil-based energy crisis, while the development of advanced photocatalytic materials for high-performance oxygen evolution from water splitting is the biggest challenge we are facing. We report the fabrication of novel g-C3N4/Ag3PO4/Ag2MoO4 ternary composite materials and the exploration of heterostructure materials for water oxidation under LED illumination. The hybridization of three semiconductors has been confirmed by microscopic study, chemical and structural analyses. Enhanced oxygen-producing activity over the obtained ternary composite photocatalysts was observed. The reasons responsible for the enhanced oxygen-evolving performance can be ascribed to the improved light absorption toward visible light, faster charge separation and charge transportation, as well as more powerful water oxidation capability originating from the in-situ construction of dual Z-scheme-type channels under visible light irradiation. The key role of in-situ formed metallic Ag as the electron mediator is suggested based on the theoretical and experimental results. The successful synthesis of fascinating ternary water oxidation photocatalysts provides new insights into the development of novel all-solid-state Z-scheme photocatalytic systems for energy and environmental applications.